2020
DOI: 10.1002/chem.202002810
|View full text |Cite
|
Sign up to set email alerts
|

Triphenylamine/Tetracyanobutadiene‐Based π‐Conjugated Push–Pull Molecules End‐Capped with Arene Platforms: Synthesis, Photophysics, and Photovoltaic Response

Abstract: p-Conjugated push-pull molecules based on triphenylamine and1 ,1,4,4-tetracyanobuta-1,3-diene (TCBD) have been functionalized with different terminal arene units. In solution, these highly TCBD-twisted systemss howeda strong internal charge transfer band in the visible spectrum and no detectable photoluminescence (PL). Photophysical and theoretical investigations revealed very short singlet excited state deactivation time of % 10 ps resulting from significant conformational changes of the TCBD-arene moiety upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 104 publications
3
27
1
Order By: Relevance
“…2 b). Similar behavior (known as solid state luminescence enhancement) has been previously reported 31 , 32 and assigned to a conical intersection (CI) between excited and ground states of the molecule in the liquid phase. To support such scenario for the TPA-T-DCV-Ph-F molecule, we performed time-dependent density functional theory (TDDFT).…”
Section: Resultssupporting
confidence: 81%
“…2 b). Similar behavior (known as solid state luminescence enhancement) has been previously reported 31 , 32 and assigned to a conical intersection (CI) between excited and ground states of the molecule in the liquid phase. To support such scenario for the TPA-T-DCV-Ph-F molecule, we performed time-dependent density functional theory (TDDFT).…”
Section: Resultssupporting
confidence: 81%
“…We also checked the inuence of the OT range separation parameter u on the resulting optimized structures. 30 Using a RSH functional oen comes along with a non-empirical tuning of u. In fact, for each specic N-electron system, an optimal value of u can be found by enforcing the exchange-correlation functional to obey the DFT version of Koopman's theorem by aligning the negative energy of the HOMO with the gas-phase vertical IP.…”
Section: Methodsmentioning
confidence: 99%
“…16 However, some examples of luminescent TCBDs in solution or in the solid state have recently been reported. [17][18][19][20][21][22][23][24][25] Nevertheless, quantum yields were often very low at room temperature and hardly higher than 1%, with the exception of the paper of Jayamurugan et al 24 where the authors claimed quantum yields up to 4.3% at room temperature in acetonitrile. In parallel of these studies, we also studied TCBDs bearing triphenylamine and fluorenyl units that showed quantum yields comprised between 2 and 6% in rigid media at room temperature.…”
mentioning
confidence: 99%